2004
DOI: 10.2320/matertrans.45.2272
|View full text |Cite
|
Sign up to set email alerts
|

Toughness of Ultrafine Grained Ferritic Steels Fabricated by ARB and Annealing Process

Abstract: A plain IF steel and a P-added IF steel having various ultrafine grain sizes from 0.24 to 11 mm were fabricated by the accumulative roll bonding (ARB) process followed by annealing. Dynamic fracture toughness of the ultrafine grained IF steels was investigated as a function of grain size by miniaturized Charpy impact test. The static strength of the IF steels significantly increased with decreasing the grain size, while the uniform elongation was limited in the ultrafine grained samples. A number of delaminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(103 citation statements)
references
References 27 publications
3
95
3
2
Order By: Relevance
“…This implies that grain refining should rather decrease the fracture toughness at low temper- atures, i.e., increase the BDT temperature, which contradicts the fact that grain refining improves the fracture toughness at low temperatures, as observed in the Charpy impact tests 11) and the present study. Suppose (i À 1) dislocations had been emitted from the crack tip.…”
Section: Dislocation Pile-up Against Grain Boundaries Andcontrasting
confidence: 49%
See 1 more Smart Citation
“…This implies that grain refining should rather decrease the fracture toughness at low temper- atures, i.e., increase the BDT temperature, which contradicts the fact that grain refining improves the fracture toughness at low temperatures, as observed in the Charpy impact tests 11) and the present study. Suppose (i À 1) dislocations had been emitted from the crack tip.…”
Section: Dislocation Pile-up Against Grain Boundaries Andcontrasting
confidence: 49%
“…One of the methods is grain refining. [7][8][9][10] Tsuji et al 11) deformed interstitial free (IF) steel by an accumulative roll-bonding (ARB) process and measured the absorbed energy at various temperatures by conducting Charpy impact tests. They demonstrated that the IF steel gained both strength as well as ductility at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests different heat treatment schedules can be explored to mitigate temper embrittlement. Other than this, Tsuji et al [81] also reported that thin lamellae with ultrafine grain size of (<2 µm) could improve impact toughness even in the presence of harmful phosphorus through the initiation of delamination during fracture. Grain boundary engineering, for example, by changing the structure of grain boundaries, is also another alternative to solve temper embrittlement in steels [82].…”
Section: Future Challenges Of Nano-scale Precipitate Strengthened Steelsmentioning
confidence: 99%
“…Ultrafine-grained (UFG) metals produced by SPD processes show high strength consistent with the Hall-Petch relationship, and they also exhibit unusual mechanical properties compared to coarse-grained metals, for instance, a sudden decrease in uniform elongation, 5,6) strain-rate sensitivity of flow stress, 7,8) and improved low-temperature toughness. 9) However, the detailed mechanisms of these unusual mechanical properties have not been fully understood yet.…”
Section: Introductionmentioning
confidence: 99%